Epistemologi Pendidikan Karakter Islami di Pondok Pesantren MBS Al Muttaqiin Gedangsari, Gunung Kidul - Sriyanta, Sriyanta; Mujiburrohman, Mujiburrohman (TSAQOFAH, 2025)
Character education is the main goal of education in Indonesia, especially in dealing with the problem of moral degeneration that occurs among students. Character education, which is often associated with personality formation, focuses on instilling ethical values ​​that are reflected in everyday actions and behaviors. This study aims to explore Islamic character education at the MBS Al Muttaqiin Islamic Boarding School, Gedangsari, Gunung Kidul, with an epistemological approach as a theoretical basis. Epistemology, which discusses the process of acquiring and validating knowledge, is applied to understand how Islamic character values ​​are taught and understood by students through an educational process based on revelation (the Qur'an and As-Sunnah) and reason. Habits such as shaking hands, praying in congregation, memorizing the Qur'an, as well as dhikr and prayer are methods used to instill Islamic character, which includes the relationship between humans and Allah (hablum minallah) and relationships between others (hablum minannas). Teachers play an important role as a source of knowledge and role models in the process of internalizing these values, as well as being figures who guide students in obtaining moral and religious knowledge. Through the epistemology of Islamic character education, this study shows that Islamic boarding schools not only shape students with good morals, but also direct them to understand and practice knowledge that is in accordance with Islamic teachings in everyday life.